Analysis Of Holland's Theory In Career Decision Making Of Vocational High School Students - Desvikayati, Ice; Daharnis; Ifdil (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
Career choice is one of the important decisions in students' lives, especially vocational students who are directed to enter the world of work after graduation. This research aims to analyze the implementation of Holland's theory in supporting vocational students' career decision making. The method used is literature review, by collecting, evaluating, and synthesizing various relevant literatures. Holland's theory, which bases on the relationship between personality type and work environment through the RIASEC model, provides a systematic framework to help students understand their potential and choose an appropriate career. The results show that the application of Holland's theory can improve students' understanding of career choices relevant to their personality types. Through personality assessment, career information provision, and systematic planning, students are guided to make more mature and purposeful career decisions. The implementation of this theory not only helps students reduce confusion in choosing a career but also prepares them to face the challenges of the world of work. The conclusion of this study confirms that Holland's theory is an effective approach in career guidance services for vocational students. This theory is relevant to be applied in helping students understand the relationship between their potential and the world of work, as well as supporting better career decision making.